EFEKTIVITAS MEDIA PEMBELAJARAN MAGNETIC FIELD METER BERBASIS ARDUINO UNTUK MENINGKATKAN HASIL BELAJAR FISIKA SISWA SMA/MA - Aghnia Nadhira Afa; Ahmad Fahruddin; Dadi Rusdiana; Maryam Musfiroh (Karst: Jurnal Pendidikan Fisika dan Terapannya, 2023)
The Effectiveness of Arduino-Based Magnetic Field Meter as Learning Media to Improve Physics Learning Outcomes of SMA/MA Students. This study aims to determine the effectiveness of Arduino-based magnetic field meter as learning media to improve physics learning outcomes for SMA/MA students. This research is an experimental research with one group pretest posttest research design. The sample of this research was 24 students of XII MIPA from one of the MA in Garut. Data were analyzed using the <g> calculation to determine the level of improvement in student learning outcomes. Based on the data analysis, the result of the calculation <g> was 0.9118, which means that the increase in student learning outcomes was in the high category. It can be concluded that the Arduino-based magnetic field meter as learning media is effective for improving student learning outcomes in magnetic field subject.